Accuracy of robot-assisted pedicle screw insertion in adolescent idiopathic scoliosis: is triggered electromyographic pedicle screw stimulation necessary? - Shaw, K. Aaron (J Spine Surg, 2018)
BACKGROUND: Screw malpositioning is an identifiable cause of intraoperative neurophysiologic changes. Although triggered screw electromyography (t-EMG) has been found to exhibit high sensitivity for identifying malpositioned screws, no previous study has assessed the utility of combining t-EMG with robotic-assisted pedicle screw placement for identifying malpositioned screws. We sought to evaluate the utility of t-EMG used in combination with robotic-assisted pedicle screw placement for identifying malpositioned screws in patients with adolescent idiopathic scoliosis (AIS). METHODS: Patients undergoing robotic-assisted posterior spinal fusion with pedicle screw fixation for AIS underwent retrospective review from a single surgeons prospectively collected database. Preoperative demographic data and curve characteristics were recorded. Computed tomography (CT) scans were reviewed, measuring pedicle width and classifying pedicle morphology using the channel classification system. Pedicle data was compared against intra-operative t-EMG data, with a minimal threshold of 8 mA used for screw removal and screw path examination and the rate of screw re-direction recorded. All pedicle screws were verified using image intensification. RESULTS: Forty-nine patients (11 males, 38 females, average age 14.49 years) with an average curve magnitude of 51 degrees and placement of 844 pedicle screws to attain an average curve correction of 67.7%. The incidence of an absent pedicle (type C or D morphology) was 2%. Overall, 24 screws (2.8%) were identified with an abnormal t-EMG threshold. All screws were found to have an intact medial wall upon probing and were reinserted without re-direction. No patient or curve characteristic was predictive of abnormal t-EMG amplitude but smaller pedicles correlated with smaller amplitudes. CONCLUSIONS: With precise pre-operative planning, robotic-assisted pedicle screw placement has shown to be a safe and effective method in treating AIS patients as shown by the lack of medial pedicle breach and malpositioned screws. We found no evidence to support combined use of t-EMG for identifying medially malpositioned screws.